The Status of women in Philippine society [videorecroding] traditions, realities, prospects - Kintanar, Thelma B.; University of the Philippines (Diliman) Center for Women's Studies (Quezon City The Center)
Documents prospects for women in Philippine society, the considerable gains they made in the last decade such as the formulation of Philippine Development Plan for Women, 1989-1992, the passing of pro-women laws as well as gains in organizing education and research.
VHS.
In-charge of photography, Ma. Christina Saulo.
Keywords: Feminism -- Philippines; Women -- Legal status, laws, etc. -- Philippines; Women -- Social conditions. -- Philippines; Women -- Philippines